2007
DOI: 10.1016/j.jvs.2007.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results with laser atherectomy in the treatment of infrainguinal occlusive disease

Abstract: These data demonstrate that laser atherectomy can be used with high initial technical success rate. Chronic renal failure and diabetes are risk factors for a negative outcome. Poor results in patients with diabetes and renal failure necessitate careful case selection in this subgroup, in which laser atherectomy is less likely to provide a definitive revascularization result or limb salvage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 31 publications
4
31
0
Order By: Relevance
“…In this regard, a reduction of target lesion revascularization has been reported with the use of drug-eluting stents 36-38 or laser atherectomy. 39 …”
Section: Study Limitationsmentioning
confidence: 99%
“…In this regard, a reduction of target lesion revascularization has been reported with the use of drug-eluting stents 36-38 or laser atherectomy. 39 …”
Section: Study Limitationsmentioning
confidence: 99%
“…48 Furthermore, Stoner et al reported an overall 12-month patency rate of 44% in treating 47 FP and infrapopliteal lesions with the laser. 49 Finally, in the CELLO (Clirpath Excimer Laser System to Enlarge Lumen Openings) trial, 65 FP de novo lesions were treated with excimer laser. Patency rates were 59 and 54% at 6 and 12 months, respectively.…”
Section: Biological Factorsmentioning
confidence: 99%
“…However, they also offer clinicians the potential to revascularize limbs of patients who are not optimal candidates for open bypass. Several novel endovascular therapies have garnered considerable attention, 3,4 but they also have not yet withstood the rigors of objective randomized clinical trials.…”
mentioning
confidence: 99%